FLOW OF AN EMULSION DROP THROUGH A CONVERGING CHANNEL USING THE BOUNDARY ELEMENT METHOD - Cunha, Lucas Hildebrand Pires da; Albuquerque, Eder Lima de; Siqueira, Ivan Rosa de (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
The Boundary Element Method is employed to simulate the ï¬‚ow of a planar emulsion drop through a converging channel. The physical ï¬‚ow parameters allow to describe it using Stokes equations. A verification on the method accuracy and convergence is done related to the mesh and time increment refinement. The pump pressure answer, during the drop ï¬‚ow to keep the ï¬‚ow rate, is studied in relation to the capillary number, the viscosity ratio and the drop initial diameter.